Vulnerabilidades à aquisição de HIV/AIDS na população em situação de rua em Fortaleza - Ceará - Freitas, Vívien Cunha Alves de (2022)
The aim of this study was to analyze the personal, social and programmatic vulnerabilities for STI and HIV of the homeless population. Cross-sectional study, with a quantitative and descriptive approach, carried out with 104 homeless people in the city of Fortaleza - Ceará who use the social equipment called 'Social Cafeteria'. Three instruments were used for data collection, which took place in the years 2020 to 2022: 1) structured form with closed questions about sociodemographic, sexual and reproductive data and knowledge about HIV/aids, constructed from the adaptation of the research on Brazilian sexuality and instruments used in studies at local and national levels; 2) constructed and validated instrument containing questions about the woman's sexuality, the partner's and knowledge about HIV/aids transmission and prevention; 3) Screening test for involvement with alcohol, cigarettes and other substances – ASSIST. The dependent variable considered was 'presence of previous HIV/STI'. Statistical analyzes were performed using Microsoft Excel® 2019 and R® version 4.1.0 software and the Wald Test was used, together with the associated p-value; Chi-square and Mann-Whitney tests. Logistic Regression was developed using 'stepwise' readjustment techniques. Regarding the vulnerabilities of women to HIV/STI it was found that they do not feel vulnerable, at an individual and social level, to sexually transmitted infections, as they know aspects of the infection and for not submitting to unprotected sexual practice and multiple sexual partnerships, despite the non-consistent use of preventive methods. Regarding programmatic vulnerability to HIV/STI, it was evident that prevention actions aimed at the homeless population and the community in general are carried out sporadically, without care longitudinality. Furthermore, regarding the odds of previous HIV/STI, it was found that participants with transsexual or transgender gender identity, those who had three or more casual partners and who suffered sexual violence before being on the streets, had 13.76; 9.2 and 3.6 more chances of previous HIV/STI, respectively. The most used psychoactive substances were alcoholic beverages, tobacco derivatives and cocaine/crack, so that HP experiences situations of strong desire for consumption and health, social, legal or financial problems. The results of this research will contribute to the identification and mitigation of vulnerabilities of the homeless population to HIV/aids, as well as the improvement of professional practices so that they are inclusive and contextual to the assisted population.